2022
DOI: 10.3389/fanim.2022.875572
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of L-Citrulline Changes Brain Free Amino Acid and Monoamine Metabolism in Heat-Exposed Broiler Chickens

Abstract: High ambient temperatures (HT) in summer are becoming more severe due to global warming, leading to severe adverse effects on poultry production. Recently, we have reported that oral administration of L-citrulline (L-Cit) can minimize hyperthermia in chickens under HT. However, whether oral L-Cit can enter the brain, the center for thermoregulation, has not been studied. We investigated the effects of oral administration of L-Cit on free amino acids and monoamines in the diencephalon region of the brain of hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Orally administered L-Cit can increase the concentration of Cit, Arg, and Orn in the brain under both CT and HT conditions (Chowdhury et al, 2022; Figure 2). Concentrations in the brain of tryptophan and its metabolite serotonin (5-HT) were lower under HT than under CT.…”
Section: L-cit In Thermoregulationmentioning
confidence: 98%
See 2 more Smart Citations
“…Orally administered L-Cit can increase the concentration of Cit, Arg, and Orn in the brain under both CT and HT conditions (Chowdhury et al, 2022; Figure 2). Concentrations in the brain of tryptophan and its metabolite serotonin (5-HT) were lower under HT than under CT.…”
Section: L-cit In Thermoregulationmentioning
confidence: 98%
“…Moreover, a concern with dietary Arg supplementation is its potential antagonism with basic amino acids, including Arg, lysine, and histidine, whereas Cit is a neutral amino acid and does not share the same transporters with basic amino acids (Wu & Morris, 1998). It was further reported that oral administration of L-Cit significantly increased plasma and brain Arg, Orn, and Cit (Chowdhury et al, 2022). Therefore, Cit administration may be helpful in chickens to minimize heat stress and to increase plasma Arg.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation